2019
DOI: 10.1111/cen.13955
|View full text |Cite
|
Sign up to set email alerts
|

Is calcium supplementation always needed in patients with hypoparathyroidism?

Abstract: Summary Oral calcium salts are recommended for the treatment of chronic hypoparathyroidism (HypoPT), although dosimetry is variable between individual patients and clinicians. However, patient feedback on calcium salts can be negative, particularly due to gastrointestinal side effects and hypercalciuria‐related complications. We begin with a clinical case of a HypoPT patient taking oral calcium salts following thyroid surgery, who requested support in reducing her dose of these with a view to stopping entirely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In our group of patients, all had a rather high calcium intake with only little variability between patients, making it difficult to detect differences in a relative small sample size. A recent study from United Kingdom showed that patients with chronic HypoPT sometimes can be well managed by active vitamin D alone without any calcium supplements and that relief from using (high doses of) calcium supplements is preferred by the patients 18 . Accordingly, we do not believe that our findings should be interpreted in such a manner that calcium intake is not important.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In our group of patients, all had a rather high calcium intake with only little variability between patients, making it difficult to detect differences in a relative small sample size. A recent study from United Kingdom showed that patients with chronic HypoPT sometimes can be well managed by active vitamin D alone without any calcium supplements and that relief from using (high doses of) calcium supplements is preferred by the patients 18 . Accordingly, we do not believe that our findings should be interpreted in such a manner that calcium intake is not important.…”
Section: Discussionmentioning
confidence: 69%
“…A recent study from United Kingdom showed that patients with chronic HypoPT sometimes can be well managed by active vitamin D alone without any calcium supplements and that relief from using (high doses of) calcium supplements is preferred by the patients. 18 Accordingly, we do not believe that our findings should be interpreted in such a manner that calcium intake is not important. Larger studies including patients with a more diverse intake should be performed in order to test this hypothesis.…”
Section: F I G U R Ementioning
confidence: 76%
“…obstipation, fl atulence and others), risk for vascular calcifi cations and renal stones [17][18][19]. Diff erent strategies have been implemented by other authors to overcome these worries -alternate calcium intake or even "no calcium" regimens [20,21]. The most common worries about calcitriol are kidney damage and polyuria as already reported in a diff erent study with 64 patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…( 12 Another potentially contentious point is that the Bollerslev guideline mandates the use of oral calcium salts but a growing body of evidence conflicts with this view suggesting that oral calcium salts are not necessarily routine and are only recommended for patients with a dietary calcium deficiency. 14 Finally, the methodology necessarily includes an element of "self assessment" and this too may have the potential to skew the data.…”
Section: Discussionmentioning
confidence: 99%